2017
DOI: 10.1039/c6cp08704c
|View full text |Cite
|
Sign up to set email alerts
|

Interpolated energy densities, correlation indicators and lower bounds from approximations to the strong coupling limit of DFT

Abstract: We investigate the construction of approximated exchange-correlation functionals by interpolating locally along the adiabatic connection between the weak- and the strong-coupling regimes, focussing on the effect of using approximate functionals for the strong-coupling energy densities. The gauge problem is avoided by dealing with quantities that are all locally defined in the same way. Using exact ingredients at weak coupling we are able to isolate the error coming from the approximations at strong coupling on… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
105
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 35 publications
(114 citation statements)
references
References 74 publications
6
105
1
Order By: Relevance
“…This has been recently used for constructing XC functionals from a local interpolation along the adiabatic connection. 14,2729 Although this approach is promising for treating strong correlation within the realm of DFT, 14 it can still easily overcorrelate (for example for stretched bonds it overcorrelates the fragments), again because the SCE (exact or approximate) quantities are often far from the physical ones. 29 …”
mentioning
confidence: 99%
See 3 more Smart Citations
“…This has been recently used for constructing XC functionals from a local interpolation along the adiabatic connection. 14,2729 Although this approach is promising for treating strong correlation within the realm of DFT, 14 it can still easily overcorrelate (for example for stretched bonds it overcorrelates the fragments), again because the SCE (exact or approximate) quantities are often far from the physical ones. 29 …”
mentioning
confidence: 99%
“…The XC energy densities along the adiabatic connection (i.e., position-dependent quantities w λ ( r ) that integrate to W λ [ρ] when multiplied by the density) are not uniquely defined and therefore we have to be specific on their gauge . 14,29,4345 A physically sound gauge often considered in DFT is the one of the electrostatic potential of the XC hole. 14,34,35,46 Within this gauge we can express the λ-dependent energy density in terms of the corresponding spherically averaged XC hole 14,34,35,47 h xc λ ( r , u ) obtained from |Ψ λ [ρ]| 2 ,where u = | r – r ′| is the distance from a reference electron at r .…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…It has been found that the local interpolations are in general more accurate than their global counterpart. 89 Thus, the study carried out here provides also a very useful first idea of what could be achieved with these higher-level approaches.…”
Section: Introduction and Theoretical Backgroundmentioning
confidence: 93%